Contrasting effects of soil type and use of cover crops on nitrogen and phosphorus leaching in agricultural systems of the Argentinean Pampas - Portela, Silvina Isabel; Reixachs, Carolina; Torti, Maria Juliana; Beribe, Maria Jose; Giannini, Ana Paula (Elsevier, 2024)
Agricultural systems of the Argentinean Pampas generally use rotations of summer crops under no-tillage and apply fertilization at rates that do not compensate nutrient exports with grain harvest, resulting in negative balances and soil fertility loss. However, the humid climate, long fallow periods and soil factors enhance nitrogen (N) and phosphorus (P) leaching, which has a negative impact on freshwater ecosystems. We propose to evaluate the effect of soil type and replacement of fallow periods with cover crops on drainage and N and P leaching. We used lysimeters containing two Mollisols of contrasting texture and porosity (a Typic Argiudoll and a Typic Hapludoll), and cultivated between 2014 and 2022 with a maize-soybean rotation with (M-CC-S) and without (M-S) cover crops under no tillage. The amount of drainage varied with rainfall (p<0.01), was similar between soils and higher in M-S than in M-CC-S during the intercropping period (148 vs 96 mm, p<0.05). The correlation between daily rainfall and drainage was higher for the Typic Argiudoll (r=0.46 and 0.42, for M-S and M-CC-S, respectively) than for the Typic Hapludoll (0.28 and 0.23 for M-S and M-CC-S, respectively) when considering same-day events, and it decreased for the Typic Argiudoll (r=0.31 and 0.26, for the M-S and M-CC-S, respectively) but not for the Typic Hapludoll (0.28 and 0.21 for the M-S and M-CC-S, respectively) with a 1-day lag between series. The amount of N and P lost through leaching varied with drainage (p<0.01). Cover crops reduced nitrate leaching to a greater extent in the Typic Hapludoll (from 30.4 to 3.3 kg ha−1 period−1) than in the Typic Argiudoll (from 17.6 to 2.0 kg ha−1 period−1) (p<0.05). Soil type modified P leaching in M-S (0.32 and 0.11 kg ha−1 period−1 for the Typic Argiudoll and the Typic Hapludoll, respectively) and M-CC-S had intermediate P leaching (0.17 and 0.16 kg P ha−1 period−1 for the Argiudoll and Hapludoll, respectively) (p<0.05). We conclude that: 1) water flows through different channels in each soil, the rapid flow of the Typic Argiudoll probably occurs through preferential flow channels (macropores) while the slower flow of the Typic Hapludoll is probably associated to matrix porosity, 2) P leaching is related to soil type (Typic Argiudoll > Typic Hapludoll) and drainage reduction by cover crops off-sets P leaching through macropores in the Typic Argiudoll, and 3) cover crops reduce N leaching, due to drainage reduction and N retention in cover crop biomass.